Disentangling the relationship between liquidity and returns in Latin America (2017)
We dissect the impact of liquidity on returns of Latin American firms using a detailed dataset of firm characteristics over various market cycles. We find that firm-level liquidity (illiquidity) is positively (negatively) associated with returns. Further analysis reveals that global illiquidity and endogenously determined crisis periods are negatively associated with returns. Our results are in contrast to the majority of the literature on developed markets and indicate that liquidity is less of an important risk factor in Latin America. Our results suggest that improvements in firm-level liquidity will enhance returns and reduce the vulnerability of returns to global illiquidity.